2018
DOI: 10.12998/wjcc.v6.i16.1128
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory meningococcal vaccine, and other recommended immunisations: Uptake, barriers, and facilitators among health care workers and trainees at Hajj

Abstract: AIMTo evaluate the uptake of a mandatory meningococcal, a highly recommended influenza, and an optional pneumococcal vaccine, and to explore the key factors affecting vaccination rate among health care workers (HCWs) during the Hajj.METHODSAn anonymous cross-sectional online survey was distributed among HCWs and trainees who worked or volunteered at the Hajj 2015-2017 through their line managers, or by visiting their hospitals and healthcare centres in Makkah and Mina. Overseas HCWs who accompanied the pilgrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…For HCWs deployed in Hajj, the rates of immunization in our study were similar to those reported in a study conducted in the 2015-2017 Hajj seasons. 32 However, our data indicates that the rate of immunization of influenza vaccination among the Hajj cohort was higher than that reported pre-2015. 19,20 In general, since the introduction of the compulsory BICSL license that includes the compulsory influenza and meningococcal immunization section, data from the MOH indicate that in 2017, all HCWs deployed to Hajj were vaccinated with both vaccines.…”
Section: Discussioncontrasting
confidence: 63%
“…For HCWs deployed in Hajj, the rates of immunization in our study were similar to those reported in a study conducted in the 2015-2017 Hajj seasons. 32 However, our data indicates that the rate of immunization of influenza vaccination among the Hajj cohort was higher than that reported pre-2015. 19,20 In general, since the introduction of the compulsory BICSL license that includes the compulsory influenza and meningococcal immunization section, data from the MOH indicate that in 2017, all HCWs deployed to Hajj were vaccinated with both vaccines.…”
Section: Discussioncontrasting
confidence: 63%
“…84,85 Since the inclusion of the quadrivalent meningococcal vaccine in 2001, 85 no major meningo coccal meningitis outbreaks related to hajj have been identified. [85][86][87] However, concern that new serogroups of N meningitidis (eg, B and X), which are not covered in the current quadrivalent vaccine targeting serogroups A, C, W135, and Y, could be a cause of future epidemics is increasing. 88,89 Owing to the high incidence of pertussis seen among Hajj pilgrims in 2003, 90 Bordetella pertussis is considered a risk in pilgrims, especially those who have not completed their immuni sation schedule.…”
Section: Infectious Diseases At the Hajjmentioning
confidence: 99%
“…103 For the Hajj and other mass gatherings appropriate travel advice on hygiene measures, [104][105][106][107] wearing of face masks, and recom mendations for mandatory and optional vaccines for prevention of infections are issued by local public health authorities and WHO. Occasionally authorities in countries of origin face hurdles in the implementation of these measures 87,108 or issues regarding reduced immunogenicity of vaccines owing to interactions between vaccines. 109 Although no global outbreaks of meningococcal disease have occurred after the Hajj for decades, a high level of awareness of the possibility of outbreaks at all mass gatherings remains.…”
Section: Reducing Risk Of Spread Of Infectious Diseases With Epidemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, despite being enforced and freely offered, the vaccine coverage was found to be very low (64%) in 2006 in the only published work reporting vaccine uptake among domestic pilgrims [12]. The rate was also unsatisfactory among domestic HCWs (ranging from 51.7% to 84.7%) in several studies conducted between 2009 and 2018 [17][18][19][20]. In recent years, the enforcement of the Hajj permit requirement by rigorous procedures at points of entry into Makkah reduced the number and proportion of domestic pilgrims (from 1.4 million (45%) in 2012 to 600,000 (26%) in 2018) [21].…”
Section: Introductionmentioning
confidence: 99%